Design, Modeling, and Characterization of Hot Electron Light Emission and Lasing in Semiconductor Heterostructure-VCSOA with Optical Gain up to 36 dB - Yaba, Hawro I.; Chaqmaqchee, Faten A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
Vertical-cavity semiconductor optical amplifiers (VCSOAs) are interesting devices for optical communication applications. In this work, we have studied the characteristics of gain spectra and amplifier bandwidth in reflection mode at 1300 nm GaInNAs/GaAs hot electron light emission and lasing in semiconductor heterostructure-VCSOA structure using MATLAB program. The device contains 16 Ga0.7In0.3N0.038As0.962 multiple quantum wells (QWs) in its intrinsic region; the active region is bounded between eight pairs of GaAs/AlAs top distributed Bragg reflectors (DBRs) mirror and 25 pairs of AlAs/GaAs bottom DBRs mirror. Simulation results suggest that the resonance cavity of QW of HILLISH-VCSOA is varied with temperature and number of DBRs periods. We compare the relation between the wavelength and gain at a different single-pass gain in both reflection and transmission modes. The highest gain at around 36 dB is observed in reflection mode. Moreover, we calculated the amplifier bandwidth at different periods of top mirror’s reflectivity, in which when the peak reflection gains increases, the amplifier bandwidth decreases.